2,6-Dipicolinoylbis(N,N-dialkylthioureas) as Versatile Building Blocks for Oligo- and Polynuclear Architectures - Nguyen H.H.; Jegathesh J. J.; Takiden A.; Hauenstein D.; Pham C. T.; Le C. D.; Abram U. (My University, 2016)
2,6-Dipicolinoylbis(N,N-dialkylthioureas) as Versatile Building Blocks for Oligo- and Polynuclear Architectures
Keywords: 2,6-Dipicolinoylbis